Regulation of Adipose Tissue Insulin Resistance and Diabetic Parameters in Drug Naïve Subjects with Type 2 Diabetes Treated with Canagliflozin Monotherapy - Kutoh, Eiji; Kuto, Alexandra N; Ozawa, Eri; Kurihara, Rumi; Akiyama, Midori (Drug research, 2023)
The objective of this study is to investigate the link between the baseline/changes of body weight and those of diabetic parameters during treatment with an SGLT-2 inhibitor. Drug naïve subjects with T2DM received canagliflozin monotherapy for 3 months. Adipo-IR was selected as the significant factor responsible for the changes of (Δ)BMI with this drug. While no correlations were noted between ΔBMI and ΔFBG, ΔHbA1c, ΔHOMA-R or ΔQUICKI, significant negative correlations were observed between ΔBMI and Δadipo-IR (R=-0.308). The subjects were divided into two groups with baseline BMI<25 (n=31, group alpha) or≥25 (n=39, group beta). Baseline levels of FBG, HbA1c, T-C, TG, non-HDL-C, LDL-C showed no differences between group alpha and beta. The subjects were also divided into two equal numbers of subjects (n=35 each) based on the changes of weight: the lower half (-3.6%, p<0.00001, group A) and the upper half (0.1%, n.s., group B) of ∆BMI. FBG, HbA1c or HOMA-R significantly, similarly decreased, while QUICKI increased in group A and B. TG significantly decreased, while HDL-C increased in group A. HOMA-B significantly increased, while adipo-IR insignificantly decreased in group B. Collectively, these results suggest that 1) adipose tissue insulin resistance is responsible for the weight changes with canagliflozin. 2) baseline levels of glycemic and some lipid parameters were similar between obese and non-obese populations. 3) weight changes with canagliflozin were not associated with its glycemic or insulin sensitizing efficacies but were linked to adipose-tissue insulin resistance, some lipids, and beta-cell function.